FLOUTING MAXIM ON UTTERANCE OF CHARACTERS IN "ANAK NEGERI (KISAH MASA KECIL GANJAR PRANOWO)" MOVIE - Febriyanti, Rina Husnaini (IJLECR (International Journal of Language Education and Cultural Review), 2021)
Implicature utterance that was introduced by Grice and his categorization on maxims those are quantity, quality, relevance, and manner seem interested to be studied, as the aim of this study is to find out the flouting of Grice maxims. The Method used was qualitive and data was collected from the utterances of the characters in "Anak Negeri (Kisah Masa Kecil Ganjar Pranowo)" Movie afterwards the data were categorized based on flouting maxims then displayed into percentage and reflected involved the reasons of those flouting maxims. Next, it was analyzed and presented in description explanation. The results found that the most flouting occurred is flouting of maxim quantity that is 46% where there are several reasons, they are in order to convince, to elaborate, to permit, and to empathy. And in the same time, the flouting of maxim relevance is not too far with quantity that is 41% with the purpose of using these flouting maxims are to inform, to give idea, to ask back, to calm down, to wonder, and to complement. Flouting of maxim quality is 5% and the reason found is to explain, while flouting of maxim manner is 5% too and the reason was to ask meaning. In other words, those flouting maxims occur, it must have a purpose, and depend on the context where this study is viewed in pragmatics perspective. Keywords: Flouting Grice Maxims, flouting maxim of quality, flouting maxim of quantity, flouting maxim of relevance, flouting maxim of manner